Pendapatan Usaha Pemeliharaan Sapi Bali di Kabupaten Muaro Jambi - Darmawi, Darlim (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
This  research  aims  to  find  out  the  income  and the Return Cost  Ratio  (R/C)  maintenance  of  Bali cattle business in Muaro Jambi Regency. This research used survey methods. Object  of research is the  Bali cattle  ranchers  PMUK  Program  Tunas  Jaya  farmer  groups  in  the  Village  of  Kebun  IX,   Muaro  Jambi. Respondents  of  this  research  of  11  Bali  cattle  ranchers  who  obtained  the  census.   The  analysis  used  is deskriptive analysis. To find out the income and Return Cost Ratio of the Bali cattle maintenance effort using the analysis of income (Rahim, 2007). Outpouring of work hours that are used in beef cattle raising activities then used  his standard working hours (JKP) according to Siregar (1996). While the cost  of cages and their equipments  with depreciation  calculation.  Results  showed,  that  the  maintenance  of  Bali  cattle  from  11 respondents (100%) is still a side business, and includes a category of patterns of family farming, with cattle ownership on average 5.61 ST / breeder. In maintaining cattle ranchers are still in the average age of 43.64 years (29-65) years including labor that is still produktiv age. Based on research results that the maintenance effort of Bali  cattle in Farmers Branch, Jaya can earn  positive income ie the average  of Rp. 4,950,953.65, -/year/farmer or an average of Rp. 412.579,47.-/ year/farmer.-. While the comparison (ratio) between revenue and expenses (Return Cost Ratio (R / C)) the income of Rp. 272,302,450, -/periode with expenditure (cost)  maintenance of Rp. 218,751,550, -/periode is the ratio of 1.24. This gives the sense that every capital of Rp 100, - it will generate income of  Rp 124, -